The Return to the Pampa in three Tales of Death and Blood, by Ricardo Güiraldes - López Jiménez, Tatiana (2021)
This article makes an interpretative proposal of three stories contained in Tales of Death and Blood (1915 to date not so studied, by the Argentine writer Ricardo Güiraldes (1886-1927). The corpus is part of the “return to the pampa” process carried out from the program promoted by the “martinfierrista” avant-garde generation, which will develop a critical vision around the imminent disappearance of the gaucho towards the beginning of the 20th century. The final reflections of the work highlight, among other things, the intersection between the traditional practice of the nineteenth-century gaucho and the reappropriations of Güiraldes, who, from a “nationalist-ethnicist” propposal, articulates his stories from elements such as irony, violence and social hierarchies. Finally, there is an opportunity to carry out future interpretations from a gender perspective, which has not yet been sufficiently explored for these tales.